Perlindungan terhadap Masyarakat Hukum Adat di Atas Tanah Ulayat dalam Sistem Hukum Pertanahan - Sarwani, Raden (Universitas Batanghari Jambi, 2024)
One form of wealth for the Indonesian nation is that the existence of Indigenous Law Communities (MHA) are recognized and respected as The rights of the MHA to natural resources, land, and forests have not been clearly regulated in a single legislation, but the MHA's control over customary forests is evident. Several customary forests in Kerinci Regency have been officially designated as customary forests based on the Decree of the Minister of Environment. The control of customary forests requires the recognition and affirmation of the MHA through Regional Regulations based on Law Number 41 of 1999 concerning Forestry. However, the Kerinci MHA, as the rightful owners of customary forests, have not yet received protection and recognition through Regional Regulations, which could threaten their sustainability. The research method used is empirical juridical. The research results show that customary forests in Kerinci Regency have been designated as customary forest areas or rights forests as stated in the Ministerial Decree, which recognizes the existence of the MHA as the rightful owners based on the Decree of the Regent of Kerinci. Although the Regent's Decree does not provide adequate explanations about the status, structure, and customary institutions managing the customary forests, it indirectly acknowledges the existence of the MHA entitled to the customary forests. Meanwhile, regulations on customary forest management should also be adjusted to facilitate protection mechanisms for the MHA. As the region with the most customary forests in Jambi Province, it is hoped that the Kerinci Regency Government can draft Regional Regulations concerning Indigenous Law Communities so that customary forests can be preserved and sustained for future generations.